Inflammatory microglia are glycolytic and iron retentive and typify the microglia in APP/PS1 mice. - Holland, Roland; McIntosh, Allison; Finucane, Orla; Mela-Rivas, Virginia; Rubio-Araiz, Ana; Timmons, G.; McCarthy, S.; Gunko, Y.K.; Lynch, Marina Ann (Elsevier, 2018)
Microglia, like macrophages, can adopt inflammatory and anti-inflammatory phenotypes depending on the stimulus. At the polar ends of the spectrum of phenotypes are the socalled M1-like inflammatory cells and M2-like anti-inflammatory cells that are stimulated in vitro by lipopolysaccharide (LPS) or interferon- (IFN) and interleukin-4 (IL-4) respectively. In macrophages, the evidence indicates that these phenotypes have different metabolic profiles with M1-like cells switching to glycolysis as their main source of ATP and M2-like cells utilizing oxidative phosphorylation. There is a paucity of information regarding the metabolic signatures in inflammatory and anti-inflammatory microglial phenotypes. Here, we polarized primary microglia with IFN and show that the characteristic increases in nitric oxide synthase 2 (NOS2) and tumor necrosis factor-α (TNF) were accompanied by increased glycolysis and an increase in the expression of 6- phosphofructo-2-kinase/fructose-2,6-biphosphatase (PFKFB)3, an enzyme that plays a significant role in driving glycolysis. These changes were associated with increased expression of ferritin and retention of iron in microglia. In contrast with the IFN-induced changes IL-4, which predictably increased mRNA expression of mannose receptor C, type 1 (MRC-1) and arginase 1 (Arg1), also increased oxygen consumption in microglia. The data indicate distinct metabolic signatures of inflammatory and anti-inflammatory microglia that are also distinguishable by their iron handling profiles.
The IFNg-induced shift to glycolysis in microglia is associated with changes in iron handling by cells.
https://openpolicyfinder.jisc.ac.uk/id/publication/12478
Keywords: Microglia; Glucólisis; Hierro - Metabolismo; Inflamación (Patología); Modelos animales en investigación; APP/PS1 mice; Ferritin; Glycolysis; IFNγ; Iron; Microglial activation; PFKFB3